Is the Addition of Sublingual Melatonin to Omeprazole Superior to Omeprazole Alone in the Management of Gastroesophageal Reflux Disease Symptoms: A Clinical Trial - Malekpour, Habib; Noori, Amin; Abdi, Saeed; Abbasinazari, Mohammad; Mahboubi, Arash; Ghamsari, Mahdiye Abiyar (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Proton pump inhibitors are frequently used to treat gastroesophageal reflux disease, but their effect is restricted. The present study aimed to investigate whether the addition of sublingual melatonin to omeprazole was effective in the treatment of gastro gastroesophageal reflux disease symptoms. Materials and Methods: This was a randomized double-blind clinical trial. A total of 78 patients with gastro gastroesophageal reflux disease were randomly allocated to either omeprazole 20 mg/d plus sublingual melatonin (3 mg/d) or omeprazole 20 mg/d plus placebo for 4 weeks. The selected patients had histories of heartburn and regurgitation and a score ≤32 on the Frequency Scale for the Symptoms of gastroesophageal reflux disease (FSSG). The outcome measures for the assessment of treatment efficacy were heartburn, epigastric pain and the Frequency Scale for the Symptoms of gastroesophageal reflux disease score. Safety and quality of life were evaluated in the patients as the secondary outcomes too. Results: Seventy-two out of 78 eligible patients completed this trial (35 in the melatonin group and 37 in the placebo group). Heartburn, epigastric pain, and Frequency Scale for the Symptoms of gastroesophageal reflux disease score declined significantly in the melatonin group compared to the placebo group (P = .04, P = .03, and P = .0001, respectively). Moreover, the quality of life score was significantly higher in the melatonin group compared with the placebo group (P = .0001). Adverse events were similarly observed in the 2 groups (P = .55), and there were no serious adverse events. Conclusion: The combination of sublingual melatonin (3 mg/day) with omeprazole (20 mg/day) may be more effective than omeprazole (20 mg/day) alone in the treatment of gastroesophageal reflux disease.